The Reliability of Quantifying the Pancreatic Ductus in Predicting the Operability of Pancreatic Adenocarcinomas - Abdussamet Batur; Fatma Durmaz (Journal of Contemporary Medicine, 2020)
Purpose: To evaluate the quantifying of the pancreatic ductus in predicting the operability of pancreatic adenocarcinomas Methods and Materials: We reviewed the clinical and imaging data of 30 patients (21 men, 9 women; mean age, 64.2 years; age range 41-93 years) who had histopathologically proven pancreatic head adenocarcinoma, and underwent multidetector CT for their initial nonspesific symptoms before the diagnosis was rendered. Accompanying secondary signs also were analysed. Results: Thirty patients with pancreatic head adenocarcinoma were evaluated. Thirteen of them (43.3%) were found to be operable (Group A) and seventeen of them (56.7%) were found to be inoperable (Group B) radiologically and surgically. The mean caliber of the dilated pancreatic duct in Group A patients was 5.80 mm, and in Group B pateints was 9.15 mm (p=0.001). The ratio of pancreatic duct caliber to gland width was 0.46 in Group A and was 0.62 in Group B (p=0.001). Accompanying secondary signs such as choledoch dilatation, tumor size, and initial complaints showed no significant difference between the two groups. Conclusion: The main pancreatic duct diameter and/or a ratio of duct to gland width can be useful in predicting the operability of pancreatic adenocarcinomas